The Role of Knowledge Sharing , Leader-Member Exchange (LMX) on Organizational Citizenship Behavior and Employee Performance : An Empirical Study on Public Health Center of Pati 1, Pati 2 and Trangkil in Central Java - Sa'adah, Noor; Rijanti, Tristiana (International Journal of Social and Management Studies, 2022)
he purpose of this study is to describe and analyze the effect of knowledge sharing on organizational citizenship behavior, analyze the effect of Leader-Member Exchange (LMX) on Organizational Citizenship Behavior, analyze the effect of Knowledge Sharing on performance, analyze the effect of Leader-Member Exchange (LMX) on performance, analyze the effect of OCB on Performance, analyzing the effect of Knowledge Sharing on performance with OCB mediation, analyzing the effect of Leader-Member Exchange (LMX) on performance with OCB mediation. The population of this research is the employees of Puskesmas Pati 1, Pati 2 and Trangkil as many as 165 people. The number of samples for this research is 98 respondents. In this study, the sampling technique used is simple random aside. Data collection will be carried out through an online questionnaire survey. Statistical analysis in this study uses the process of calculating researchers using the IBM SPSS Statistic Version 23 computer program. Based on the results of data analysis, it is concluded that knowledge sharing positive and significant effect on organizational commitment, knowledge sharing has a positive and significant effect on performance, leader member exchange has a positive and significant effect on organizational commitment, leader member exchange has a positive and significant effect on performance, organizational commitment has a positive and significant effect on performance, organizational commitment mediates the relationship between knowledge sharing and performance, organizational commitment mediates the relationship between leader member exchange and performance.